2010
DOI: 10.1097/inf.0b013e3181edf475
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Disease and Barriers to the Diagnosis and Treatment of Group a Beta-Hemolytic Streptococcal Pharyngitis for the Prevention of Rheumatic Heart Disease in Dar Es Salaam, Tanzania

Abstract: To understand patient and clinician attitudes toward Streptococcus pharyngitis and rheumatic heart disease prevention in Tanzania, data from 3 sources were obtained: a survey of 119 clinicians, outpatient rapid test screening, and interviews with 17 rheumatic heart disease patients. Patients do not seek care for sore throat. Clinicians stated that identifying and treating Streptococcus pharyngitis is not prioritized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…However, the immediate treatment of such superficial GAS infections is a losing game in resource-limited settings. Only few people consult medical health services for sore throat [23]. This was confirmed in our study population where only 5.9 % affirmed having sought medical consultation for tonsillopharyngitis.…”
Section: Discussionsupporting
confidence: 81%
“…However, the immediate treatment of such superficial GAS infections is a losing game in resource-limited settings. Only few people consult medical health services for sore throat [23]. This was confirmed in our study population where only 5.9 % affirmed having sought medical consultation for tonsillopharyngitis.…”
Section: Discussionsupporting
confidence: 81%
“…These observations emphasise the high frequency and poor therapeutic management of sore throat in children. A better understanding of reasons behind the difficulty of primary prevention has been recently carried out in Tanzania, emphasising the negligence of patients and also medical staff regarding the importance of consulting and treating sore throat 22. The poor management of cases of diagnosed RHD has also been highlighted in the Global Rheumatic Heart Disease Registry (The REMEDY study) where only 55% of patients were found to be receiving antibiotic treatment 23…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed elsewhere. 27,28 The same may be true for acute rheumatic fever, which can cause severe acute illness but commonly presents with subtle manifestations, especially with recurrent episodes. 29 Our study supports the notion that, to prevent rheumatic heart disease, efforts to treat streptococcal pharyngitis and acute rheumatic fever will need to be implemented in community settings.…”
Section: Discussionmentioning
confidence: 99%